2009
DOI: 10.1111/j.1478-3231.2008.01911.x
|View full text |Cite
|
Sign up to set email alerts
|

Survivin is upregulated during liver regeneration in rats and humans and is associated with hepatocyte proliferation

Abstract: Survivin is upregulated in human and rodent liver regeneration and correlates with proliferation, suggesting an association of survivin and cell division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Expression of survivin is associated with inhibition of cell death and is required for cell division (Altieri, 2008). Survivin has recently been reported to be important in liver regeneration following partial hepatectomy (Baba et al , 2009). Within 3 h of acetaminophen administration to wild type mice, we found that survivin protein expression was up-regulated in hepatocyte nuclei located adjacent to portal veins and spreading to necrotic zones in the livers by 24 h. Evidence suggests that expression of survivin is controlled by Cav-1 via the β-catenin-Tcf/Lef-dependent signaling pathway and it has been suggested that the anti-proliferative and pro-apoptotic properties of Cav-1 are due to reduced survivin expression (Torres et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of survivin is associated with inhibition of cell death and is required for cell division (Altieri, 2008). Survivin has recently been reported to be important in liver regeneration following partial hepatectomy (Baba et al , 2009). Within 3 h of acetaminophen administration to wild type mice, we found that survivin protein expression was up-regulated in hepatocyte nuclei located adjacent to portal veins and spreading to necrotic zones in the livers by 24 h. Evidence suggests that expression of survivin is controlled by Cav-1 via the β-catenin-Tcf/Lef-dependent signaling pathway and it has been suggested that the anti-proliferative and pro-apoptotic properties of Cav-1 are due to reduced survivin expression (Torres et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In regeneration experiments, we could show that the reduced hepatocyte number is likely due to decreased proliferation rather than increased cell death, as no differences in apoptosis were detected. Previous reports demonstrated that depletion of Survivin, inspite of leading to a major defect in mitosis, was not associated with an increase of apoptosis.…”
Section: Alb-survmentioning
confidence: 94%
“…19 In studies conducted in rodents, an increase in Survivin expression after partial hepatectomy was observed at postoperative days 2-3. 3,4 After split liver transplantations in humans, Survivin expression was elevated in the graft at day 5. In both settings, Survivin immunoexpression correlated with proliferation but not with apoptosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…163 In addition, survivin, a protein involved in negative regulation of program cell death, has recently been shown to be upregulated during liver regeneration and to mediate hepatocyte proliferation. 183 Finally, TGF-b1, another cytokine found upregulated after partial hepatectomy, has a central role in liver tissue remodeling events. Interestingly, TGF-b1 is involved in liver regeneration termination after liver mass recovery, 162 although its effect might be partly indirect and depend on induction of stellate cell activation and enhanced ECM synthesis (see behind).…”
Section: Liver Regeneration: a Good Reason For Choosing Liver Models mentioning
confidence: 99%